A DECADE ANALYSIS OF THE IMPACT OF VILLAGE FUND ON POVERTY: A BIBLIOMETRIC APPROACH - Saksono, Lalang; Wodi , Lidya Chatrine; Sari , Santi Retno; Digdowiseiso , Kumba (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Research on village funds in Indonesia became increasingly widespread after a law on village funds was passed in 2014. Village funds are a program that is expected to positively impact village development by alleviating poverty and equalizing income. This research aims to systematically map the direction of research results on village funds and poverty using quantitative review techniques. This research is a type of systematic literature research using bibliometric VOSviewer. Data collected from 2014 to 2023 resulted in 472 articles eligible for processing. The results show that the development of village fund research related to poverty is quite saturated and has been widely carried out. This research is increasing from year to year, and the current direction of the topic of village funds is mostly related to transparency and allocation. It is necessary to fill the gap in research on village funds and poverty with empirical research and include a more complete model with mediation and moderation.